Association Between Levels of N-Terminal Pro-brain Natriuretic Peptide and Coronary Artery Lesion in Patients with Kawasaki Disease: A Systematic Review and Meta-analysis - Xinle Xu; Jin Wang (Archives of Rheumatology, 2025)
Background/Aims: Kawasaki disease (KD) is often complicated by coronary artery lesions (CAL). Identifying reliable biomarkers may improve early diagnosis and risk stratification for CAL, facilitating timely intervention. This study aims to investigate the diagnostic value of N-terminal pro-brain natriuretic peptide (NT-proBNP) in KD complicated with CAL. Materials and Methods: PubMed, Scopus, Web of Science, Embase, and the Cochrane Library databases were searched from inception to November 30, 2024 for English-language studies comparing NT-proBNP levels in KD patients with and without CAL. Diagnostic accuracy metrics for NT-proBNP in detecting CAL were also analyzed. The analysis was performed using a random-effects model. I² statistics assessed heterogeneity. NT-proBNP levels reported as medians were converted to means using established formulas. Results: Nineteen studies involving 9017 participants showed significantly higher NT-proBNP levels in KD patients with CAL (pooled standardized mean differences = 1.889, 95% CI: 1.274 to 2.504, P < .001), with substantial heterogeneity (I² = 98.5%). Eighteen studies assessed diagnostic accuracy, yielding pooled sensitivity and specificity of 0.78 (95% CI: 0.68–0.85) and 0.78 (95% CI: 0.70–0.84), respectively. The diagnostic odds ratio was 12 (95% CI: 7–21), with an AUROC of 0.85 (95% CI: 0.81–0.88). Heterogeneity remained significant (I² = 99%). Conclusion: NT-proBNP is a promising biomarker for detecting CAL in KD, with good diagnostic accuracy. Its role is best realized as part of a multimodal diagnostic approach. Future research should focus on standardization and validation across diverse populations.